RELIGIOSITY AS A MEDIATION OF EMOTIONAL INTELLIGENCE AND BULLYING IN MTSS UMMI LUBUK PAKAM STUDENTS - Fadlul Hayat Lubis; Suryani Hardjo; Yudistira Fauzi Indrawan (Jurnal As-Salam, 2026)
This study analyzes the mediating role of religiosity in the relationship between emotional intelligence and bullying among students at MTsS Ummi Lubuk Pakam. Employing structural equation modeling-partial least squares (SEM-PLS) with SmartPLS software, the results indicate that emotional intelligence has a significant negative effect on bullying (T-statistic = 8.191; p-value = 0.000) and a significant positive effect on religiosity (T-statistic = 6.944; p-value = 0.000). Furthermore, religiosity was found to have a significant negative effect on bullying (T-statistic = 5.576; p-value = 0.000). Mediation analysis confirmed that religiosity significantly mediates the relationship between emotional intelligence and bullying (T-statistic = 4.314; p-value = 0.000). It implies that emotional intelligence reduces bullying not only directly but also indirectly by fostering increased religiosity. This research highlights the importance of developing emotional intelligence and nurturing religiosity as effective strategies for bullying prevention in schools.